“Kyrie paschale” in Polish Organ Tablatures from the First Half of the 16th Century – Problems of Style and Attribution - Grzegorz Kos (Muzyka)
This article is devoted to an analysis of the intabulations of the ‘Kyrie paschale’ preserved in the so-called Lublin Tablature and in an organ tablature from the monastery of the Canons Regular of the Holy Ghost in Cracow. The intabulations are arrangements of consecutive sections of the plainchant melody Kyrie ‘Lux et origo’ and constitute sequences of segments (or modules) of a Mass in which organ music alternates with plainchant. In total, the two tablatures contain more than twenty segments of the ‘Kyrie paschale’ for organ, made up of ten modules repeated in transpositions and as variants combined to form various sequences and signed with three inconsistently ascribed attributes: N.C. (Nicolas Cracoviensis?), phÿnk (Heinrich Finck) and Josquin (Josquin des Prez).